Comparative analysis of soil analysing datas on different sempling-plots - Víg, Róbert; Dobos, Attila (Acta Agraria Debreceniensis, 2006)
Hibrid maize is cultivated on larger plots, therefore the sown areas of hibrid maize are heterogeneous from a pedology aspect. Heterogenity causes problems during tasseling, chemical plant protection and harvest. The heterogenity of sown areas can be compensated by fertilization which is based on soil analysis. We carried out research into change of the soil on four soil types from 1987 to 2005.There were no significant changes in pH, hydroiodic acidity, CaCO3-content, humus-content on meadow chernozem soil. We detected equalization of salin content in the examined soil layers. There were no significant changes in the measured values on chernozem meadow soil and solonetz meadow soil in 2005. We discoverd equalization of saline content on chernozem meadow soil, but the changes were not as obvious as the changes on meadow chernozem soil. We found salinization in the 30-60 cm soil layer on type meadow soil that may be due to water movement.